2014
DOI: 10.1158/2326-6066.cir-13-0227
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Binding Properties of Tumor Neoepitopes in Humans

Abstract: Cancer genome sequencing has enabled the rapid identification of the complete repertoire of coding sequence mutations within a patient’s tumor and facilitated their use as personalized immunogens. While a variety of techniques are available to assist in the selection of mutation-defined epitopes to be included within the tumor vaccine, the ability of the peptide to bind patient MHC is a key gateway to peptide presentation. With advances in the accuracy of predictive algorithms for MHC class I binding, choosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 45 publications
10
137
0
Order By: Relevance
“…36 This test using a gold standard set of neoantigens confirms that our pipeline largely classifies true positives correctly. A prospective prediction of neoepitopes followed by functional validation showed that 6% (3/48) of our predicted epitopes were associated with neoantigen-specific T-cell responses in patientscomparable to the rate of 4.8% found recently for melanoma.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…36 This test using a gold standard set of neoantigens confirms that our pipeline largely classifies true positives correctly. A prospective prediction of neoepitopes followed by functional validation showed that 6% (3/48) of our predicted epitopes were associated with neoantigen-specific T-cell responses in patientscomparable to the rate of 4.8% found recently for melanoma.…”
Section: Discussionsupporting
confidence: 52%
“…We applied NetMHCpan prospectively to 31 of 91 CLL cases for which HLA typing information was available 26 to predict the binding affinities of peptides generated by somatic mutation to each patient's MHC class I alleles, because this algorithm consistently performs with high sensitivity and specificity across HLA alleles. 21,35,36 Based on standard criteria in the field, we considered peptides with IC 50 , 150 nM as strong binders, IC 50 of 150 to 500 nM as intermediate to weak binders, and IC 50 .500 nM as nonbinders. 29 For the 31 cases, we found a median of 10 strong (range, 2-40) and 12 intermediate to weak binding peptides (range, 2-41) per case.…”
mentioning
confidence: 99%
“…However, the potential of neoantigen-specific T cells to induce tumor regression is largely unexplored (4). Neoepitopes may vary in their suitability as target (5), but identifying suitable epitopes remains difficult because in vitro analysis of T cells often cannot predict in vivo efficacy (6). Similarly, although T cells against neoepitopes are not subjected to central tolerance mechanisms, their fate in cancer-bearing individuals is unclear, as is the functional quality of T cell receptors (TCRs) obtained from individuals with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…27,[29][30][31] In subsequent studies in humans it has then been demonstrated that tumor sequencing data can also be exploited in a clinical setting, and that neoantigens serve as tumor-rejection antigens. 30,[32][33][34][35] As no standard treatment for metastatic NETs was established yet, and because NETs are known to be highly heterogeneous and unique regarding the genomic landscape, we suggest, that a personalized treatment strategy, targeting patient-specific neoantigens, might be an appropriate approach.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, it was controversially discussed among researchers, whether enhancement of an existing T cell response or generation of de novo responses is clinically relevant for an effective tumor vaccine. 35 Carreno et al recently reported that neoepitope vaccination not only can amplify existing CD8 C T cell responses but also can produce responses that might have been silent prior to vaccination. 38 Thus, even if no T cell reactivity was seen for certain neoepitopes in the ELISpot assays, vaccination with them might still generate potent antitumor T cell responses.…”
Section: Discussionmentioning
confidence: 99%